2016
DOI: 10.1183/16000617.0036-2016
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic mechanisms in pulmonary arterial hypertension: the need for global perspectives

Abstract: Pulmonary arterial hypertension (PAH) is a severe and progressive disease, characterised by high pulmonary artery pressure that usually culminates in right heart failure. Recent findings of alterations in the DNA methylation state of superoxide dismutase 2 and granulysin gene loci; histone H1 levels; aberrant expression levels of histone deacetylases and bromodomain-containing protein 4; and dysregulated microRNA networks together suggest the involvement of epigenetics in PAH pathogenesis. Thus, PAH pathogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…While numerous studies have outlined the epigenetic mechanisms in pulmonary hypertension (reviewed in [ 56 , 57 , 58 , 59 ]), the epigenomic regulation in systemic hypertension remains largely undescribed. Due to the well-known involvement of the renin-angiotensin-aldosterone system (RAAS) system on arterial pressure regulation, the effects of epigenomic regulation of the RAAS system have been extensively tested in animal models of systemic hypertension [ 4 ].…”
Section: Epigenomic Regulation In Hypertensive Vasculaturementioning
confidence: 99%
“…While numerous studies have outlined the epigenetic mechanisms in pulmonary hypertension (reviewed in [ 56 , 57 , 58 , 59 ]), the epigenomic regulation in systemic hypertension remains largely undescribed. Due to the well-known involvement of the renin-angiotensin-aldosterone system (RAAS) system on arterial pressure regulation, the effects of epigenomic regulation of the RAAS system have been extensively tested in animal models of systemic hypertension [ 4 ].…”
Section: Epigenomic Regulation In Hypertensive Vasculaturementioning
confidence: 99%
“…MicroRNAs (miRNAs) are endogenous small noncoding RNAs (∼22 nt) that negatively regulate gene expression by binding to the 3′ untranslated region (3′-UTR) of their target coding mRNA to inhibit expression by blocking translation and/or accelerating mRNA degradation 3 . A growing number of studies have reported that specific miRNAs can improve the outcome of PAH, suggesting that miRNAs may play a role in the pathogenesis of PAH 4 , 5 . Recent studies have shown that the miR-125a-5p plays a key role in several regulatory processes, including the proliferation, migration, and apoptosis of various cell types, thereby affecting the development of certain diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Anticipation might be explained by cumulative genetic damage or by some other mechanism besides a trinucleotide repeat. Recent work suggests a role for epigenetic, such as DNA methylation, in the pathogenesis of PAH [14]. In ammatory and hypoxic milieu might in ict oxidative damage to DNA.…”
Section: Discussionmentioning
confidence: 99%